2016
DOI: 10.1007/s10997-016-9364-2
|View full text |Cite
|
Sign up to set email alerts
|

Minority and majority private equity investments: firm performance and governance

Abstract: This paper adds to the literature on the determinants of the effects of private equity (PE) investments. Using an original dataset of 191 target firms in Italy, we study the effects on performance and governance of the stakes acquired by the PE investor. We employ a difference-in-differences approach and compare target and control firms sharing similar characteristics and performance in the years preceding the deal. We find that PE investment has a positive effect on profitability, sales, and employment; these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…The empirical evidence varies on PE active investor's impact on the target's operational and accounting performance. Battistin et al (2017) found a positive impact of PE investments on the target firm's sales and profitability in the case of minority interest investments, but did not provide an evidence of a significant change in sales and EBITDA (earnings before interest, taxes, depreciation and amortization) if a PE investor acquired a majority stake (50% and more) in a target company. Clifford (2008) reported that companies targeted by blockholder activists experienced improvements in operational efficiency as a result of activist investments compared to firms targeted by passive investors.…”
Section: Private Equity Activism and Target Companies' Performancementioning
confidence: 76%
“…The empirical evidence varies on PE active investor's impact on the target's operational and accounting performance. Battistin et al (2017) found a positive impact of PE investments on the target firm's sales and profitability in the case of minority interest investments, but did not provide an evidence of a significant change in sales and EBITDA (earnings before interest, taxes, depreciation and amortization) if a PE investor acquired a majority stake (50% and more) in a target company. Clifford (2008) reported that companies targeted by blockholder activists experienced improvements in operational efficiency as a result of activist investments compared to firms targeted by passive investors.…”
Section: Private Equity Activism and Target Companies' Performancementioning
confidence: 76%
“…While it is commonly assumed that family firms are reluctant to hand over control to outside investors (La Porta, Lopez-De-Silanes, & Shleifer, 1999;Mahérault, 2004;Poutziouris, 2001;Wu, Chua, & Chrisman, 2007), more and more private family firms open their capital for external investors (Battistin, Bortoluzzi, Buttignon, & Vedovato, 2017;Dawson, 2011;Wessel, Decker, Lange, & Hack, 2014). This evolution is driven by trends in both the demand and supply of capital.…”
Section: Governance Implications Of Attracting External Equity Investors In Private Family Firmsmentioning
confidence: 99%
“…The insights also call for research that takes new theoretical perspectives to study owner dynamics in private firms. While research in this area is largely dominated by agency theory (Battistin et al, 2017;Chrisman, Chua, Steier, Wright, & McKee, 2012;Daily, Dalton, & Cannella, 2003), our model calls for better integrations with alternative theoretical perspectives. Second, our study contributes to the family business literature by examining gradual transitions from a family to a non-family firm.…”
Section: Governance Implications Of Attracting External Equity Investors In Private Family Firmsmentioning
confidence: 99%
See 2 more Smart Citations